2009
DOI: 10.1101/gr.093237.109
|View full text |Cite
|
Sign up to set email alerts
|

Deeply conserved chordate noncoding sequences preserve genome synteny but do not drive gene duplicate retention

Abstract: Animal genomes possess highly conserved cis-regulatory sequences that are often found near genes that regulate transcription and development. Researchers have proposed that the strong conservation of these sequences may affect the evolution of the surrounding genome, both by repressing rearrangement, and possibly by promoting duplicate gene retention. Conflicting data, however, have made the validity of these propositions unclear. Here, we use a new computational method to identify phylogenetically conserved n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 80 publications
0
56
1
1
Order By: Relevance
“…Hufton et al even propose that the gene balance hypothesis better explains gene duplication retention in vertebrate genomes than the DDC model (Hufton et al, 2009). In their study of phylogenetically conserved noncoding sequences, they showed that genes retained after WGD are rather marked by many protein interaction sites than by many conserved noncoding elements, as the DDC model would predict (Hufton et al, 2009).…”
Section: Gene Dosage Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hufton et al even propose that the gene balance hypothesis better explains gene duplication retention in vertebrate genomes than the DDC model (Hufton et al, 2009). In their study of phylogenetically conserved noncoding sequences, they showed that genes retained after WGD are rather marked by many protein interaction sites than by many conserved noncoding elements, as the DDC model would predict (Hufton et al, 2009).…”
Section: Gene Dosage Effectsmentioning
confidence: 99%
“…In their study of phylogenetically conserved noncoding sequences, they showed that genes retained after WGD are rather marked by many protein interaction sites than by many conserved noncoding elements, as the DDC model would predict (Hufton et al, 2009). Additionally, it is plausible that an increased dose of some genes is beneficial even if they are not highly interactive.…”
Section: Gene Dosage Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Ultra-Deep CNSs Are Conserved in Both Rice and Arabidopsis Animal CNEs can be detected between mammals and the early diverging chordate amphioxus, lineages that diverged ;520 mya (Hufton et al, 2009). To test whether any of the deep CNSs discovered in eudicots are also conserved in monocots (diverged ;140 mya), we added orthologous rice genes to GEvo panels containing deep eudicot CNSs (Supplemental Figure 1).…”
Section: Deeply Conserved Plant Cnss Are Located Closer To Their Cognmentioning
confidence: 99%
“…In the largest study conducted to date, more than 40% of 150 human-fugu CNEs tested had enhancer activity versus only 5% of human-rodent CNEs (Visel et al, 2007). Similarly, 45% of 22 CNEs conserved between the invertebrate amphioxus (Branchiostoma floridae) and vertebrates (mouse, fugu, and zebra fish [Danio rerio]) had enhancer activity in a transgenic zebra fish assay (Hufton et al, 2009). …”
Section: Introductionmentioning
confidence: 99%